The Impact of Selected School Experiments on Pupils’ Attitudes Toward Chemistry - Ilić, Božidar; Subotić, Siniša; Balaban, Milica; Zeljković, Saša (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2025)
School experiments, as a teaching method, represent one of the visual ways of explaining relevant natural phenomena to pupils. The application of experiments in chemistry teaching is often interpreted as an excellent way to achieve good learning outcomes. The impact of conducted school experiments on pupils was examined using psychological instruments, administered before and after performing the selected school experiments in front of the pupils. Feedback from 143 respondents, pupils from primary and secondary schools in Bosnia and Herzegovina, was collected. Adequate statistical analysis was performed. Two key measures were identified: Affinity towards Chemistry and positive experiment experience. A slight but significant increase in the affinity scores was noted after demonstrating school experiments, showing a mildly positive impact on students' attitudes toward chemistry. Positive Experiment Experience scores were high, indicating a favorable perception of the demonstrations. The data suggest that students' initial affinity towards chemistry is the best predictor of their attitudes after the experiment, suggesting that pre-existing attitudes are key. No evidence was found for a "magic" intervention that significantly changes students' affinity. These findings highlight the importance of continuous engagement over isolated demonstrations, which alone cannot replace the impact of ongoing work with students.